Let’s assume that Y gets ₹x and Z gets ₹y.

According to the given information, X gets three-fifths of what Y gets. So, X gets (3/5)x.

The ratio of the share of Y to Z is 6:11. So, we can write it as x:y = 6:11.

Now, let’s calculate the total amount of money distributed: x + (3/5)x + y = ₹2060 (8/5)x + y = ₹2060

Also, we know that x:y = 6:11. So, we can write it as x/y = 6/11.

Now, let’s solve these two equations to find the values of x and y.

From the equation x/y = 6/11, we can rewrite it as x = (6/11)y.

Substituting this value of x in the first equation, we get: (8/5)(6/11)y + y = ₹2060 (48/55)y + y = ₹2060 (103/55)y = ₹2060 y = (₹2060 * 55) / 103 y ≈ ₹1100

Now, substituting the value of y in the equation x = (6/11)y, we get: x = (6/11) * ₹1100 x ≈ ₹600

So, X gets ₹600, Y gets ₹1100, and Z gets the remaining amount: Z = ₹2060 - (₹600 + ₹1100) Z = ₹2060 - ₹1700 Z = ₹360

Therefore, X gets ₹600, Y gets ₹1100, and Z gets ₹360.